Ring opening of benzoxazinones: An improved and efficient synthesis of clavatustides A & B. Issue 35 (30th August 2017) - Chettu, Suresh Kumar; Konidena, Lakshmi Narayana Sharma; Korupolu, Raghu Babu; Kameswara Rao, N.S.; Doddipalla, Raju; Gandham, Hima Bindu; Guduru, Ramakrishna
Graphical abstract: Highlights: An alternative method for the esterification of α-hydroxyesters has been developed. Ring opening of benzoxazinones with α-hydroxy esters was demonstrated. Synthesis of clavatustides A and B was achieved in 4 steps with good overall yield. Both enantiomers or clavatustides A and B synthesized using the newly developed method. Abstract: Ag2 O mediated esterification of ( R )- tert -butyl 2-hydroxy-3-phenylpropanoate has been realized via the effective ring opening of benzoxazinones that resulted in the efficient synthesis of cyclodepsipeptides clavatustides A and B and their enantiomers in very good overall yields.